Zoneamento geoambiental da bacia do rio Fartura: abrangendo os municípios de São José do Rio Pardo-SP, São Sebastião da Grama-SP, Vargem Grande do Sul-SP e Águas da Prata-SP, na escala 1:50.000 - Faleiros, Cássia de ávila Ribeiro Junqueira (Universidade Federal de São Carlos, 2012)
Grounded on geo-environmental zoning, this study seeks to contribute to the discussion about environmental management in light of sustainable development, thus bringing together economic development and environmental constraints. The 227km2 study area the Fartura river basin comprises the municipalities of Sao Jose Do Rio Pardo, Sebastiao da Grama, Vargem Grande do Sul, and Aguas da Prata, in the State of Sao Paulo, Brazil. The purpose of this study is to propose ways to organize activities as the populations of these municipalities increase, thereby promoting sustainable occupation of the physical environment in accordance with existing urban planning guidelines and legislation. To this end, geo-environmental zoning of this river basin was conducted by means of remote sensing and geo-processing (GIS) technologies. From cartographic documentation and field/lab work results, an environmental diagnosis was produced, including information relevant to environmental planning of the watershed in question. During prognosis, several occupation scenarios for the Fartura river basin were worked out for the 1987, 2000, and 2010 periods. They shed light on the urban expansion dynamics, land use/economic activities, and native vegetation conservation patterns of these municipalities. This prognosis ultimately indicated emerging occupation trends for this river basin and brought about guidelines for land-use planning. Moreover, it was possible to verify that its bedrock is quite homogeneous, 70% of which pertaining to the Varginha Complex. With regard to its soil texture, it was found that 47% of the Fartura river basin soil is sandy and that 86% of the soil composition of the total watershed area is over 50% sand. As to its declivity, it was shown that although 14% of the water basin area displays declivities higher than 30%, most of which falls within the 5%-20% declivity range. This factor, along with its soil texture, suggests a high likelihood of erosion processes happening in this water basin. In addition, inappropriate land use in APPs (Permanent Conservation Areas) can lead to erosion and silting in sections of the watershed area where sandy soil prevails and to flooding where more clayey soils occur. It was also attested that 35% of the area has induced occupation and 24% restricted occupation. The remaining sections should be occupied in a controlled manner under specific conditions and their use should combine farming with cattle-raising, with a view to both land rotation and soil fertility. Level sections of the Fartura river basin area may profit from mechanized farming, to which soil management/conservation techniques must be applied. As to urban occupation, the area under study showed a gradual increase (1.19%).
Geo-environmental zoning of fartura river basin, encompassing the municipalities of São José do Rio Pardo, Sebastião da Grama, Vargem Grande do Sul, and Águas da Prata, in São Paulo state, Brazil, at 1:50,000 scale
Keywords: Planejamento físico-ambiental; Zoneamento ambiental; Bacias hidrográficas; Sistemas de informação geográfica; ENGENHARIAS